The Impact of Learning and Modularity on Production Ramp-UP Performance - Li, Kunlian (2019)
In today’s rapidly changing business environment, the case for accelerated New Product Development (NPD) has become increasingly compelling at both a theoretical and practical level. As one of the most important production processes before the launch of new products, ramp-up has become a key for enterprises to accelerate NPD. Poor ramp-up performance could contribute to the failure of making profit for the new product. However, approximately 60% of enterprises failed to maximize their ramp-up performance (Bischoff, 2007; Li et al., 2014). In contemporary studies, learning is one of the most concerned factors studied by researchers that affect ramp-up performance. Also, in order to reduce costs and production time, more and more manufacturing companies begin to incorporate product and process modularity into the R&D and production stages. Therefore, the purpose of this study is to explore whether learning and modularity can improve ramp-up performance. Furthermore, although modularity has improved the company's performance, its impact on learning has also been regarded as of concern to manufactures during the ramp-up phase. This study also explores how modularity plays a moderating role in the relationship between leaning and ramp-up performance. Empirical data were collected from five cases of traditional and electronic Chinese manufacturing industries. The result demonstrates that learning has a positive impact on ramp-up performance and modularity can reduce production time and promote product quality which means improving ramp-up performance as well. Moreover, modularity has a negative moderating effect on internal learning but appears to play a facilitating role in promoting the ramp-up performance improved by external learning. The results of this study provide practical suggestions for manufacturing enterprises which apply modularity to improve their ramp-up performance. Such enterprises can improve their ramp-up performance by adopting modularity and learning as hybrid systems in production because the improvement of modularity does not always hinder learning's impact on ramp-up. Thus, the manufacturing companies can explore a way to improve ramp-up performance by combining modularity and learning to make the trade-off between "long-term learning" and "rapid returns".